„Das Leben ist kurz“ – Verjüngung und Unsterblichkeit aus historischer Perspektive - Schäfer, Daniel (DMW - Deutsche Medizinische Wochenschrift, 2017)
To be young and immortal: That is the dream of humanity. Medical and civilizing progress have led to a life expectancy unthinkable a few centuries ago. Physicians wonder where it will all end. And after all, does it make sense to live forever? A look back in history and literature can help to relativize (post) modern utopias.
Keywords: Lebensverlängerung; Verjüngung; Unsterblichkeit